Safety and efficacy of a feed additive consisting of Lacticaseibacillus rhamnosus (formerly Lactobacillus rhamnosus) IMI 507023 for all animal species (ALL‐TECHNOLOGY (IRELAND) LIMITED [Alltech Ireland]). (23rd July 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Lacticaseibacillus rhamnosus (formerly Lactobacillus rhamnosus ) IMI 507023 as a technological additive for all animal species. The additive is intended to improve the production of silage at a proposed application rate of 1 × 10 9 colony‐forming units (CFU)/kg fresh material. The bacterial species L. rhamnosus is considered by EFSA to be suitable for the qualified presumption of safety approach. As the identity of the strain has been established and no acquired antimicrobial resistance determinants of concern were detected, the use of the strain as a silage additive is considered safe for livestock species, for consumers and for the environment. In the absence of data, the FEEDAP Panel cannot conclude on the potential of the additive to be a skin/eye irritant or a skin sensitiser. Given the proteinaceous nature of the active agent, the additive should be considered a respiratory sensitiser. The additive at the proposed application rate of 1 × 10 9 CFU/kg fresh material has the potential to improve the fermentation of the silages from easy to moderately difficult to ensile forages.